CURRENT STATUS OF NURSING SCIENTIFIC RESEARCH AT THONG NHAT HOSPITAL IN THE PERIOD 2021-2023 - Thị Thơi, Lê; Thị Thảo Sương, Nguyễn; Thị Thuận, Vũ (Journal of Health and Aging, 2025)
Describe the current situation and analyze some factors affecting participation in scientific research of nurses at Thong Nhat Hospital in the period 2021-2023. A cross-sectional descriptive study was conducted on 335 nurses in clinical departments and in-depth interviews with Hospital Leaders, Department/Office Leaders, Department Head Nurses and nurses. The rate of nurses participating in scientific research is 25.37% (n = 85). Of the 85 nurses participating in research, the rate of participation in 2 or more topics is 45.88%. Nurses are the project leaders of 16.4%. Scientific research activities of nurses are mainly data collection (85.9%), accounting for the highest rate compared to other activities. The number of scientific articles with the participation of nurses is low, accounting for 13.46% (21/156 articles in 3 years). Factors affecting nurses' participation in scientific research: professional qualifications, work position, knowledge, attitude, skills in scientific research, scientific research training activities participated. The proportion of nurses participating in scientific research is low, and their main activity is data collection. Professional qualifications, working position, knowledge, attitude, and skills in scientific research, funding, the role of hospital leaders/department leaders, reward policies for science and technology, and annual competition review activities are factors that influence nurses' participation in scientific research.
Keywords: Scientific research; nurses